The Strategic Role of Debt in Takeover Contests - CHOWDHRY, BHAGWAN; NANDA, VIKRAM (Journal of Finance, 1993)
ABSTRACT In a takeover contest, the presence of bidders' existing debtholders, if they can be expropriated by issuing new debt with equal or senior priority, allows bidders to commit to bid more than their valuation of the target. Such commitment can be beneficial because it deters potential entry by subsequent bidders and may allow a first bidder to acquire the target at a bargain price. The cost is that if entry by subsequent bidders does nevertheless take place, because the first bidder has committed himself to bid high premia, a bidding war ensues resulting in offers that may involve excessive premia, i.e., bids that are larger than the bidders' valuation of the target.